ردود على أوهام حول حق حرية المرأة في الإسلام - Zawawi (زواوي) (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2013)
In the western, is still evolving paradigm that discredit Islam to curb the freedom of women and demeaning position. Consequently, there is a movement for